2014
DOI: 10.1007/s10841-014-9720-y
|View full text |Cite
|
Sign up to set email alerts
|

Bowling for bees: optimal sample number for “bee bowl” sampling transects

Abstract: The use of bowl traps to sample bee diversity has become common in recent years. To provide guidance in optimizing bee bowl sampling effort, we used several independent datasets from North America (Pacific Northwest golf courses, suburban Maryland, and Chihuahuan Desert) to estimate the number of bowls in a sampling event at which additional bowls added little to estimates of species richness or to cumulative species lists. We examined changes in the value of a nonparametric richness estimator (Chao2) as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
3
23
1
1
Order By: Relevance
“…The results of this study do agree with the heterogeneity required in sampling intensity in other systems, suggesting that sampling intensity should be considered in experimental design when the study taxa are diverse or dynamic (e.g., Shapiro et al. ). Temporal variation may drive some of the differences in the sampling required to fully describe the bee diversity in each orchard, although four of the six sites where the year‐to‐year variation was lower than the regional variation were undersampled.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results of this study do agree with the heterogeneity required in sampling intensity in other systems, suggesting that sampling intensity should be considered in experimental design when the study taxa are diverse or dynamic (e.g., Shapiro et al. ). Temporal variation may drive some of the differences in the sampling required to fully describe the bee diversity in each orchard, although four of the six sites where the year‐to‐year variation was lower than the regional variation were undersampled.…”
Section: Discussionsupporting
confidence: 81%
“…Neither orchard size nor percent agriculture in the surrounding landscape bears a relationship to the proportion of expected species richness in our apple orchards, so the mechanism driving the need for some orchards to be more heavily sampled is still unclear. The results of this study do agree with the heterogeneity required in sampling intensity in other systems, suggesting that sampling intensity should be considered in experimental design when the study taxa are diverse or dynamic (e.g., Shapiro et al 2014). Temporal variation may drive some of the differences in the sampling required to fully describe the bee diversity in each orchard, although four of the six sites where the year-to-year variation was lower than the regional variation were un-dersampled.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Shapiro et al (2014) suggested that the optimal sample number for bee bowl sampling transects is 30 bowls but the effect of sample number has not been tested in the neotropics, then our results can be considered not reliable in terms of sample number alone. But even considering that a high number of samples can retrieve a larger proportion of aculeate community, the sampling interval remains crucial to deal with phenology because the insect communities are strongly affected by seasonal and interannual fluctuations (OERTLI et al, 2005).…”
Section: Discussionmentioning
confidence: 75%